(untitled) (Research, Society and Development, 2020)
Currently, new concepts, ideas and definitions about religion, religiosity and spirituality are traced by Anthropology, Sociology, Psychology and have gained new spaces and meanings in modern society. Spirituality can be perceived as a possible dimension of the subject, linked to his experiences and beliefs, and it can be understood as a health promoting aspect in the human being when it is related to a positive attitude of affirmation of life on the part of the person who experiences it. In particular, health professionals should understand and welcome sick people in their unique ways of dealing with the disease, and this premise is necessary for establishing the therapeutic link under the integrality perspective. The purpose of this article is to reflect on the interface between spirituality and health as a possibility of meanings linked to human experiences. To this end, an exploratory bibliographic research was carried out on academic texts, books, newspapers, electronic libraries and databases in scientific publications - repositories and indexers (BVS, CAPES journals, PubMed) that provide materials for addressing the proposed theme. Finally, it is suggested the inclusion of this topic in the education of health professionals, considering that the issue of spirituality will arise in the daily life when dealing with health users.